Supranationality and international organizations: definition, features, models - Mykhailo M. Mykievych, Olha M. Shpakovych, (Opción, 2020)
The purpose of the article is to investigate the concepts of supranationality as a special phenomenon and category of modern international law, to distinguish its features, models and to analyze the problem of the relation of supranationality with the state sovereignty. It is argued that the ratio of supranationality to the bodies of international organizations and the sovereignty of the Member States in the process of regulating certain spheres of society contributes to the formation of a new perspective. Supranationality is serving as a factor and manifestation of integration and globalization processes, an evolutionary method of finding acceptable forms of deepening state cooperation.